2022
DOI: 10.1038/s41598-022-23696-7
|View full text |Cite|
|
Sign up to set email alerts
|

RAB27A promotes the proliferation and invasion of colorectal cancer cells

Abstract: Colorectal cancer (CRC) is one of the most commonly diagnosed cancer types worldwide. Despite significant advances in prevention and diagnosis, CRC is still one of the leading causes of cancer-related mortality globally. RAB27A, the member of RAB27 family of small GTPases, is the critical protein for intracellular secretion and has been reported to promote tumor progression. However, it is controversial for the role of RAB27A in CRC progression, so we explored the exact function of RAB27A in CRC development in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In some studies, Rab27a is demonstrated to regulate exosome production and metastasis. Disrupting Rab27a expression reduces exosome release, tumor growth, and metastasis in melanoma, pancreatic cancer and colorectal cancer [ 39 41 ]. In our study, we demonstrated that miR-124-3p inhibits Rab27a expression via directly targeting its 3′-UTR, which inhibiting the exosome secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, Rab27a is demonstrated to regulate exosome production and metastasis. Disrupting Rab27a expression reduces exosome release, tumor growth, and metastasis in melanoma, pancreatic cancer and colorectal cancer [ 39 41 ]. In our study, we demonstrated that miR-124-3p inhibits Rab27a expression via directly targeting its 3′-UTR, which inhibiting the exosome secretion.…”
Section: Discussionmentioning
confidence: 99%
“…As stated before, Rab-GTPase families are involved in EV release; thus, inhibiting Rab proteins can block EV secretion [ 243 ]. Rab27A knockdown has been illustrated to curtail growth and invasion of CRC cells, while Rab27A overexpression restored this effect [ 244 ]. Sulfisoxazole, a sulfonamide antibacterial, disrupts EVs biogenesis and attenuates exosomal PD-L1 expression by reducing Rab27A in colon cancer cells, thereby synergistically improving anti-PD1 therapy response [ 245 ].…”
Section: Therapeutic Application Of Sevs In Crcmentioning
confidence: 99%
“…Generation and release of exosomes involves several Rab GTPase proteins, such as Rab11, Rab27, and Rab35 [17]. Rab27a controls exosome secretion in several types of cancer, increases proliferation and invasion, decreases apoptosis, and results in resistance to the cisplatin therapy [18][19][20]. Previous studies have reported that Rab27a promoted cell proliferative, migratory, invasive, and epithelialmesenchymal transition phenotypes in HCC [21,22].…”
Section: Introductionmentioning
confidence: 99%